İmece as Collaboration: Azra Erhat’s Collaborative Retranslation Projects - Berk Albachten, Özlem (TTR, 2024)
This article situates collaborative (re)translation in the first decades of the Turkish Republic within a wider concept of imece (collective work), which sought to modernize the country in every field. İmece translations, produced primarily by the state-governed Translation Bureau (1940-1966), were wide-ranging endeavours that included the selection of texts, the creation of translations by several actants (who often contextualized the translations with paratexts), and the publishing of such translations. Within this context, the focus of the article is Azra Erhat, a distinguished translator, intellectual, and academic trained in this environment, where translation was not seen as a profession executed in solitude, but one that required the help and input of other agents as part of a broader cultural program. It explores two of her well-documented imece retranslations to shed light on these collaborative projects: Homer’s Iliad and Sappho’s poems, which she translated with two established poets, A. Kadir and Cengiz Bektaş, respectively. The article also discusses issues regarding subjectivity and retranslation as revealed in many of Erhat’s paratextual and extratextual statements, argues for a wider definition of subjectivity beyond the translation act, and establishes completeness, accuracy, and direct translation from the source text as the main motivations for retranslation.